2004
DOI: 10.1073/pnas.0405219101
|View full text |Cite
|
Sign up to set email alerts
|

De novo protein synthesis is required for activation-induced cytidine deaminase-dependent DNA cleavage in immunoglobulin class switch recombination

Abstract: Activation-induced cytidine deaminase is required for the DNA cleavage step of Ig class switch recombination (CSR). However, its molecular mechanism is controversial. RNA-editing hypothesis postulates that activation-induced cytidine deaminase deaminates cytosine in an unknown mRNA to generate a new mRNA encoding an endonuclease for CSR and thus predicts that DNA cleavage depends on de novo protein synthesis. On the other hand, DNA deamination hypothesis proposes that DNA cleavage is initiated by cytosine deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…We have shown that DSB associated with SHM depends on de novo protein synthesis but not on UNG. These features are the same as reported for CSR (24,25) and consistent with the RNA editing hypothesis but not with the DNA deamination hypothesis. Because AID has N-and C-terminal domains that are specifically required for SHM and CSR, respectively (10, 26), we proposed that AID interacts with SHM-and CSR-specific cofactors at the N and C termini, respectively.…”
Section: Aid-dependent ␥-H2ax Focus Formation On Ig Genes In Shm-indusupporting
confidence: 88%
See 2 more Smart Citations
“…We have shown that DSB associated with SHM depends on de novo protein synthesis but not on UNG. These features are the same as reported for CSR (24,25) and consistent with the RNA editing hypothesis but not with the DNA deamination hypothesis. Because AID has N-and C-terminal domains that are specifically required for SHM and CSR, respectively (10, 26), we proposed that AID interacts with SHM-and CSR-specific cofactors at the N and C termini, respectively.…”
Section: Aid-dependent ␥-H2ax Focus Formation On Ig Genes In Shm-indusupporting
confidence: 88%
“…ChIP was done as described (24,25). Nonspecific ␥-H2AX focus formation was induced by treatment of cells with 0.5 M staurosporine for 2 h as a positive control (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several hypotheses about how AID functions, data are accumulating that suggest that AID deaminates cytosine to uracil on the non-template strand of DNA during transcription (10). It is also possible that AID deaminates cytidine to uridine on an unknown mRNA (11,12). Data are still emerging that suggest AID has different roles and cofactor interactions when participating in CSR and SHM (13,14).…”
mentioning
confidence: 99%
“…1b). The idea of an mRNA-editing function for AID is supported by the structural similarity of AID to APOBEC-1, an apolipoprotein B-editing enzyme, and the finding that de novo protein synthesis is required for CSR and for the formation of DNA repair γ-H2AX (phosphorylated H2AX, a mammalian core histone H2A variant) foci in the immunoglobulin heavy chain (Igh) locus 3 .…”
Section: Hhs Public Accessmentioning
confidence: 99%